Assessment of using EZ-Prog: an easy color schematic model for programming problem solving - Siti Nordianah Hai Hom; Hasnul Hadi Ibrahim; Abrizah Ibrahim; Mudiana Mokhsin; Corrienna Abdul Talib (Penerbit Universiti Kebangsaan Malaysia, 2020)
Excellent academic achievement can have a great impact on matriculation students and influence their decision-making in the next step at the university and the future. However, poor problem-solving skills in programming subjects makes it difficult to make good decisions. Therefore, this study was conducted to identify the effect of using EZ-Prog in programming problem-solving learning among matriculation students. Students were guided by the color scheme model during the programming problem-solving process. The study population came from the Kolej Matrikulasi Johor (KMJ) and the sample involved was the 91 students from the One-Year Science Program, Module Two. The experiments were conducted in three weeks. The pretest and posttest question set consisted of three subjective questions and classified into three levels of difficulty according to Bloom's Taxonomy. Data were analyzed using SPSS. The results showed that there was a significant difference between the pre and posttest results after using the EZ-Prog. This demonstrates the EZ-Prog technique used in learning programming problem-solving learning enhances student problem-solving skills. The implications of this study indicate that EZ-Prog can be used in learning and teaching algorithms, especially programming problems. Finally, the positive findings from the use of EZProg indicate that this technique can be used as an innovative in teaching programming as it enhances problem-solving skills among students. This method is not limited to matriculation students, but also all students that learn a programming language and not limited to one programming language.